Copper Sulfide Based Heterojunctions as Photocatalysts for Dyes Photodegradation - Isac, Luminita; Cazan, Cristina; Enesca, Alexandru; Andronic, Luminita (Frontiers in Chemistry, 2019)
The presence of toxic, non-biodegradable and harmful organic pollutants in soils, wastewater, and atmosphere has become an indisputable and global fact as a significant environmental problem. The heterogeneous photocatalysis, an advanced oxidation process (AOP) using semiconductor materials as catalysts, is a topic of great interest considering the possibility of the pollutants removal from water. The photocatalytic degradation of different organic contaminants (dyes, pesticides, phenolic compounds etc.) present in water using semiconductor materials depends on a number of parameters such as: the bandgap energy, phase composition, crystallinity, morphology, surface area, electron-hole recombination rate, intensity of light, and adsorption capacity of the dye on the photocatalyst surface. One of the important constraints related to the catalyst photocatalytic efficiency is the fast recombination of the photogenerated electrons and holes. Therefore, various strategies have been involved in promoting the charge separation, including the development of heterojunction between two semiconductor materials, by tailoring the photocatalysts properties. This mini-review deals with the recent developments on dyes photodegradation using as catalysts various heterojunctions based on copper sulfide nanostructures, such as copper sulfide/metal oxide, copper sulfide/metal sulfide, copper sulfide/graphene, copper sulfide/organic semiconductors etc. The effects of different parameters, such as synthesis parameters, particle size, bandgap energy, surface area and morphology on the photocatalytic activity of copper sulfide heterojunctions for dyes degradation is also highlighted.